ANALISIS FUNGSIONALISME STRUKTURAL UNTUK MELIHAT OPTIMALITAS PELAKSANAAN GERBANG SALAM DI PAMEKASAN - Ibnu Ali; Ali Tohir (Research Institute and Community Engagement of IAIN MADURA, 2018)
This research is aimed to find out the obstacles that cause the implementation of Gerbang Salam is not optimal and how to make a formulation for optimizing this movement. This research is focused more on the theory of functionalism in the perspective of Talcott Person and Robert K. Merton. From Parson will be taken the theory of AGIL (adaptation, goal attainment, integration, and latent). And from Robert K. Merton will be taken theory of a thought of functions, dysfunctions, manifest functions and latent functions.Through AGIL analysis is known that the social system built on Islamic values has lost its balance. That is because these parts have experienced the dysfunctions, especially in the function of goal attainment and integration. So that the implementation of Gerbang Salam does not work optimally.